The racial test score gap and parental involvement in Britain - Eleonora Patacchini; Yves Zenou (Institute for the Study of Labor (IZA), 2007)
We investigate the racial gap in test scores between black and white students in Britain both in levels and differences across the school years. We find that there is an increasing racial gap in test scores between ages 7 and 11, and a decreasing one between ages 11 and 16. Using the richness of information of the National Child Development Study, we find that the evolution of the racial test score gap reflects the racial parenting gap. The latter can, in turn, be explained by the fact that, during this period, the social structure of black families has gone through important changes while it has remained roughly the same for white families.
urn:nbn:de:101:1-2008042281
Keywords: 330; Bildungsniveau; Ethnische Gruppe; Weiße; Farbige Bevölkerung; Familiensoziologie; Vergleich; Großbritannien